PERBEDAAN SENSITIVITAS TANGAN DAN KAKI SEBELUM DAN SESUDAH DILAKUKAN TERAPI PIJAT REFLEKSI PADA PENDERITA DIABETES MELITUS TIPE II - Resi ' Lisanawati; Yesi ' Hasneli; Oswati ' Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The purpose of this research was to identify the differences of the sensitivity level of hand and foot before and after reflexology therapy in patients with diabetes melitus type 2. The research used was quasy experiment design with non-equivalent control group. Sample of this research was 30 respods taken based on inclusion criteria using purposive sampling. The experimental group were given interventions with reflexology tools “APIYU II” three days in 1 week. Univariate and bivariate analysis was conducted using dependent sample t test and independent sample t test. The result showed that reflexology therapy effective toincreasing the hand and  foot sensitivity in patients with diabetes mellitus type 2 with p value  0,000 (<0,05). The research recomended that foot and hand reflexologi as one of the nursing intervention to improve the hand and  foot sensitivity for patients with diabetes mellitus type 2.   Keywords: Diabetes mellitus, Foot sensitivity, Hand sensitivity, Reflexology therapy